Principal's Human Resources Management Practices and Goal Achievement in Private Secondary Schools in Kwara State - Olaifa, Adeseko Sunday; Oluwaseyi Are, Godwin; Olayinka Oba, Abdulraheem; Haruna Sani, Lauratu; Wuraola Garba, Khadijah (Jurnal Pembelajaran dan Riset Pendidikan, 2025)
This study examined principals' human resource management practices and their impact on goal achievement in private secondary schools in Kwara State. Guided by three purposes, two research questions, and one hypothesis, a descriptive survey of a correctional type was used. The population included 5,784 teachers from 255 private senior secondary schools in Kwara State, per the 2019/2020 Kwara State School Census Report. A sample of 180 respondents, including teachers and principals, was selected. Data was collected through a structured questionnaire titled “Principal's Human Resources Management Practices and Goal Achievement Questionnaire” (PHRMPGAQ), based on a 4-point Likert scale. Descriptive statistics, including mean and standard deviation, were used to answer the research questions, while the hypothesis was tested using Pearson Product Moment Correlation at a 0.05 significance level. Three experts from the Department of Education Management and Counselling at Al-Hikmah University validated the instrument, and reliability was confirmed with Cronbach’s alpha values of 0.82 and 0.84. Findings indicated a high level of principals' human resource management practices in these schools and a significant relationship between these practices and goal achievement. It is recommended that principals regularly evaluate recruitment, training, appraisal, and promotion practices to ensure they effectively support the continuous achievement of educational goals.